2023
DOI: 10.1002/chem.202203990
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Machine‐Learning Enhanced Quantum Chemistry and Microwave Spectroscopy to Conformational Landscape Exploration: the Paradigmatic Case of 4‐Fluoro‐Threonine

Abstract: A combined experimental and theoretical study has been carried out on 4‐fluoro‐threonine, the only naturally occurring fluorinated amino acid. Fluorination of the methyl group significantly increases the conformational complexity with respect to the parent amino acid threonine. The conformational landscape has been characterized in great detail, with special attention given to the inter‐conversion pathways between different conformers. This led to the identification of 13 stable low‐energy minima. The equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“… 92 Replacement of conventional methods by the explicitly correlated (F12) variants 93 , 94 leads to our current standard version of the approach, which is referred to as junChS-F12. 42 , 58 , 60 Comparison with the most accurate results available for a panel of representative noncovalent complexes provided an average absolute error smaller than 10 cm –1 . 41 , 42 , 60 …”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“… 92 Replacement of conventional methods by the explicitly correlated (F12) variants 93 , 94 leads to our current standard version of the approach, which is referred to as junChS-F12. 42 , 58 , 60 Comparison with the most accurate results available for a panel of representative noncovalent complexes provided an average absolute error smaller than 10 cm –1 . 41 , 42 , 60 …”
Section: Methodsmentioning
confidence: 93%
“…In particular, the CBS extrapolation by the standard n –3 two-point formula employs MP2/jun-cc-pV­(X+d)­Z energies with X = T and Q, whereas the CV contribution is incorporated as the difference between all-electron (ae) and fc MP2 calculations, both with the cc-pCVW­(T+d)­Z basis set . Replacement of conventional methods by the explicitly correlated (F12) variants , leads to our current standard version of the approach, which is referred to as junChS-F12. ,, Comparison with the most accurate results available for a panel of representative noncovalent complexes provided an average absolute error smaller than 10 cm –1 . ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of initial structures to be considered is left to the user, but in this case, Sci-Finder was employed to obtain a large number of initial structures. An automatic procedure based on genetic algorithms guiding semi-empirical methods [ 72 , 73 , 74 ] is currently under development.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the CBS extrapolation by the standard n –3 two-point formula employs MP2/jun-cc-pV­(X+d)­Z energies with X = T and Q, whereas the CV contribution is incorporated as the difference between all-electron (ae) and fc MP2 calculations, both with the cc-pCVW­(T+d)­Z basis set . Replacement of conventional methods by the explicitly correlated (F12) variants , leads to our current standard version of the approach, which is referred to as junChS-F12. A comparison to the most accurate results available for reaction energies and activation barriers ,, showed that junChS-F12 energy evaluations at rDSD optimized geometries provide average absolute errors of the order of 1 kJ mol –1 . Therefore, this approach was employed for all of the stationary points in conjunction with anharmonic zero-point vibrational energy corrections computed in the framework of the second-order vibrational perturbation theory employing rDSD anharmonic force fields.…”
Section: Computational Detailsmentioning
confidence: 99%